A Proposal for Structuring Monitoring and Control Systems of Navigation in the Traffic Lane Next to the Port of Split - Komadina, Pavao; Rudan, Igor; Frančić, Vlado (Promet - Traffic&Transportation)
The paper introduces a feasible frame for the reorganizationand control of sea navigation (VIS system) in the accesswatenvay to the port of Split. In the paper a proposal for the introductionof a routing system on the traffic lane next to the portof Split is presented. A high-grade monitoring of seagoing navigationmeans increased safety and a higher protection of themarine environment. In this sense the validity of structuring avrs system in the controlled area results from the ever-increasingnumber of transiting vessels, some of which carrying dangerouscargoes with the majority being leisure craft and passengerships. The need for installing the system arises as well fromthe unfavorable hydrographic conditions which affect navigationand reduce the level of safety in the traffic lane next to theport of Split. The described proposal of the VIS system foreseesthe opening of new navigable routes with radar and AISequipments to be included for vessel monitoring. Their locationand mode of operation are worked out in detail in this paper.